PENGEMBANGAN MULTIMEDIA PEMBELAJARAN EKONOMI SMA/MA DENGAN MATERI PERMINTAAN DAN PENAWARAN - Fitria Endang Susana; Muhsinatun Siasah Masruri (Universitas Negeri Yogyakarta, 2015)
Penelitian ini bertujuan untuk (1) menghasilkan multimedia pembelajaran ekonomi kelas X SMA/MA dengan materi permintaan dan penawaran dan (2) mengetahui kelayakan dan efektivitas multimedia tersebut untuk meningkatkan hasil belajar ekonomi. Jenis peneli-tian ini adalah penelitian dan pengembangan yang terdiri atas tiga tahapan, yaitu penyu-sunan program/konsep, pengembangan produk dan evaluasi. Tahap penyusunan program/ konsep meliputi penentuan tujuan pembelajaran, perumusan materi pembelajaran, penentu-an strategi pembelajaran, serta mendesain dan merumuskan evaluasi formatif dan menetap-kan aplikasi. Langkah kedua adalah pengembangan produk yang meliputi pembuatan desain media (storyboard dan flowchartview), pengumpulan bahan (material collecting), dan assembly atau pengorganisasian bahan ke dalam tampilan. Proses berikutnya adalah evaluasi produk yang terdiri beberapa tahapan yaitu evaluasi ahli materi dan ahli media, uji coba perorangan, uji coba kelompok kecil, dan uji coba lapangan. Hasil uji coba menunjukkan bahwa rerata skor aspek pemograman sangat baik, materi/isi sangat baik dan aspek media/ tampilan sangat baik. Hasil penelitian menunjukkan bahwa kualitas multimedia pembelajar-an ekonomi kelas X dengan materi permintaan dan penawaran tergolong layak digunakan sebagai media pembelajaran, dan cukup efektif meningkatkan hasil belajar ekonomi.Kata kunci: ekonomi, multimedia_____________________________________________________________________ DEVELOPING ECONOMICS MULTIMEDIA FOR THEGRADE STUDENTS OF SENIOR HIGH SCHOOL/ ISLAMIC HIGH SCHOOL FOR TEACHING SUPPLY AND DEMAND Abstract This research aims at: (1) producing a multimedia for economics learning used for the grade students of Senior High School/ Islamic High School on the topic of supply and demand; and (2) finding out the feasibility and effectiveness of the interactive multimedia in improvingthe learning result of economics.This research was a Research and Development (RD) study conducted in three steps: developing/ making a concept, developing a product and evaluating the product. The first step is developing a concept which included identifying and determining the performance objective. The second is learning material, and the teaching strategies, designing the formative assessment, and production, consisting of designing the storyboard and flowchart view, and assembling or organizing the screenview materials. The next process is product evaluation which consisted of some steps: subject-matter and media expert evaluation, individual try out, small group try out, and field try out. The data were collected through a questionnaire and observation. The data are used to know the feasibility of the multimedia. Cognitive tests (pretest and posstest) are used to know the effectiveness of the interactive multimedia. The data were analyzed using the quantitative descriptive technique. The results show the average score on the instructional aspect is very good , on the concept aspect is very good and on the media aspects is very good. From this result the quality of economics multimedia for the grade students on supply and demand materials in terms of the aspects of instruction, content, and media is very good, and succed in achieving the target score.Keywords: ecomonics, multimedia.